Comparative Study of the Proximate, Mineral and Phytochemical Compositions of Avocado (Persea americana) Pulp and Seed - Kolawole, Sunday; Obueh, Henrietta; Onwuegbule, Elise (Integrated Research and Testing Laboratory (LPPT) Universitas Gadjah Mada, 2025)
The proximate, mineral and phytochemical compositions of avocado pear (Persea americana) seed and pulp were studied using standard methods. Qualitative analysis of the phytochemicals revealed the presence of flavonoids, saponin, tannins and phenols in both the seed and pulp of P. americana . Alkaloid was only present in the seed. Quantitatively, the concentration of saponins, flavoids, tannins, phenols and alkaloids in the seed were higher than in the pulp. The proximate contents (%) of the avocado seed, in decreasing order were carbohydrate (48.51± 0.56) > protein (18.08 ± 0.58) > moisture content (14.64 ± 0.38) > fat (13.31 ± 0.05), fibre (4.61 ± 0.13) > ash (0.85 ± 0.12) while the pulp had moisture content (54.27 ± 0.49%) > fat (30.85 ± 0.43%) > carbohydrate (9.33 ± 0.66%) > protein ( 2.92 ± 0.59%) > ash (1.38 ± 0.17%) > fibre (4.61 ± 0.13%). The concentration of minerals in the seed of P. americana were significantly higher (p<0.01) than in the pulp except for zinc and sodium. The P. americana seed contains higher substantial nutrients that could meet the needs and requirements of the body, thus good for human and animal consumption.